QoS SOLUTIONS FORVIDEOCONFERENCING - Zainal Abidin, Anis Zaihasmy (Universiti Teknologi Petronas, 2006)
This project is intended to gain knowledge and apply the theory leamt about the need of QoS in videoconferencing and the various options available. Today's conferencing applications are now IP friendly, it can run on either dedicated lines (like ISDN or telephone lines) or IP networks. However, as most network administrators know, conferencingapplications can wreak havoc on unprepared corporate networks. The key to successfully deploying conferencing applications is the activation of Quality of Service (QoS). QoS refers to a network's ability to reliably and consistently provide a certain level of throughput and performance. QoS for conferencing typically involves network availability, bandwidth, end-to-end delay, jitter, and packet loss. Simply stated, if the network doesn't conform to the minimum requirements in any of these areas, the conferences are doomed to fail. QoS can be achieved in a variety of ways, including over-provisioning (deploying additional bandwidth), data prioritization, and the use of QoS-enabled overlay or converged networks. Organizations have two main options for deploying QoS within their organizations; convergence or overlay. Convergence requires the use of QoS-capable WAN links throughout the organization. In many cases, this requires a fork-lift upgrade and migration of all network resources, which can place convergence out of reach of many cost-sensitive organizations. On the other hand, overlay networks allow a step-by-step migration from a non-QoS to a QoS network without the high cost and inherent risk of major network reconfigurations. In this way, overlay networks are a first step toward convergence